PENGARUH MEDIA PEMBELAJARAN DALAM TATARAN STRATEGI PEMBELAJARAN TPS (THINK- PAIR - SHARE) TERHADAP AKTIVITAS BELAJAR SISWA SMA MITRA INALUM - Irwansyah Irwansyah (Universitas Negeri Medan, 2016)
This research was aimed to know the best learning strategy between the cooperative learning strategy type TPS with animation media, cooperative learning strategy type TPS with static picture media, and conventional learning strategy to the learning activity of XI grade students in State Senior High School of Mitra inalum. This research was conducted with quasi experiment methods with three classes which sample randomly, XI IA.1 class with cooperative learning strategy type TPS with animation media; XI IA. 2 class with , cooperative learning strategy type TPS with static picture media, and XI IA. 3 class with conventional learning strategy. The observation of student learning activity done by three observer that occur in every meeting. The techique of analysis used analysis of varians with SPSS 17.0 for Windows. The result of this research and test shows the best learning strategy to get student learning activity is cooperative learning strategy type TPS with animation media, continued by cooperative learning strategy type TPS with static picture media, and then with conventional learning strategy. There are differences between learning activity XI grade students in State Senior High School of Medan thay by used the cooperative learning strategy type TPS with animation media, cooperative learning strategy type TPS with static picture media, and conventional learning strategy (F= 8.084 P= 0.001); Kata Kunci : Pembelajaran Kooperatif tipe TPS, Media Animasi, Media Gambar Diam, Aktivitas Siswa